SUSTAINABLE RESOURCE MANAGEMENT: BRIDGING COMMUNITY ENGAGEMENT AND ENVIRONMENTAL RESILIENCE IN A CHANGING CLIMATE - Kavitha Chrisnasamy; Nur Jahan Ahmad, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This review explores the critical intersection of sustainable resource management, community engagement, and environmental resilience within the context of climate change. It emphasizes the vital role local communities play in managing resources sustainably and presents case studies demonstrating successful engagement strategies from various regions, including Timor-Leste and Malaysia. The review identifies significant challenges such as capacity limitations and sociocultural barriers, while also showcasing innovative frameworks and adaptive management practices that enhance resilience. Key insights indicate that fostering collaborative governance and integrating traditional knowledge are essential for the development of effective resource management policies. Overall, this synthesis provides valuable implications for policymakers and practitioners aiming to address the complexities of resource management in a changing climate.